Reasons for participating and not participating in a e-health workplace physical activity intervention. Issue 4 (4th November 2014) - Bardus, Marco; Blake, Holly; Lloyd, Scott; Suzanne Suggs, L.
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to investigate the reasons for participating and not participating in an e-health workplace physical activity (PA) intervention. Design/methodology/approach – Semi-structured interviews and two focus groups were conducted with a purposive sample of employees who enrolled and participated in the intervention and with those who did not complete enrolment, hence did not participate in it. Data were examined using thematic analysis according to the clusters of "reasons for participation" and for "non-participation". Findings – Reported reasons for participation included a need to be more active, to increase motivation to engage in PA, and to better manage weight. Employees were attracted by the perceived ease of use of the programme and by the promise of receiving reminders. Many felt encouraged to enrol by managers or peers. Reported reasons for non-participation included lack of time, loss of interest towards the programme, or a lack of reminders to complete enrolment. Practical implications – Future e-health workplace behavioural interventions should consider focusing on employees' needs and motivators to behaviour change, provide regular reminders for participants to complete enrolment and ensure that procedures are completed successfully. Barriers to participation could be identified through formative research with the target population and feasibility studies. Originality/value – This study combines a qualitative analysis of the reasons why some employees decided to enrol in a workplace PA intervention and why some others did not. This study highlights factors to consider when designing, implementing and promoting similar interventions and that could inform strategies to enhance participation in workplace PA interventions.